2021
DOI: 10.1109/access.2021.3099795
|View full text |Cite
|
Sign up to set email alerts
|

A Stacking Ensemble Prediction Model for the Occurrences of Major Adverse Cardiovascular Events in Patients With Acute Coronary Syndrome on Imbalanced Data

Abstract: The major adverse cardiovascular events (MACE) often occur with high morbidity and mortality globally. It is very important to predict the MACE occurrences accurately in patients with acute coronary syndrome (ACS). Therefore, this paper proposes a stacking ensemble model for the prediction of MACE occurrences in patients with ACS at early stage. Our research contents are given as follows. First, we use Korea Acute Myocardial Infarction Registry National Institutes of Health (KAMIR-NIH) dataset and experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…It emphasizes that the stability of non-acute coronary heart disease is only relative, and there is a risk of progression to Acute coronary syndrome at any time, which leads to cardiovascular events ( Steg et al., 2007 ). Acute coronary syndrome is also a common subcategory of cardiovascular disease and has led to increased mortality globally ( Zheng et al., 2021 ). Acute coronary syndrome is a set of signs and symptoms due to acutely decreased blood flow in the coronary arteries, and the exact mechanism underlying its pathogenesis remains to be fully elucidated ( Dai et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It emphasizes that the stability of non-acute coronary heart disease is only relative, and there is a risk of progression to Acute coronary syndrome at any time, which leads to cardiovascular events ( Steg et al., 2007 ). Acute coronary syndrome is also a common subcategory of cardiovascular disease and has led to increased mortality globally ( Zheng et al., 2021 ). Acute coronary syndrome is a set of signs and symptoms due to acutely decreased blood flow in the coronary arteries, and the exact mechanism underlying its pathogenesis remains to be fully elucidated ( Dai et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data sampling is an efficient and valuable technique for the transformation of an imbalanced training dataset into balanced class distribution either by increasing the minority class data (oversampling), or decreasing the majority class data (undersampling), or using both strategies at the same time (hybrid sampling). From previous studies of health informatics research and data sampling techniques [ 39 , 40 , 41 , 42 ], it has been concluded that hybrid sampling techniques are considered the best data sampling techniques. According to our target variables, our final prediction results include the ACS outcomes along with the discharge reason and death type (final diagnosis + discharge result + death type) for the patients admitted to hospital due to heart problems.…”
Section: Methodsmentioning
confidence: 99%
“…The meta-learner is then trained to optimally combine the predictions of base-learners , to form a final set of predictions. An example of its use in medical research is to predict occurrences of major adverse cardiovascular events in patients with acute coronary syndromes [33] . A simplified diagram of stacking is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%